PENGARUH MODEL PEMBELAJARAN TALKING STICK TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMP NEGERI 10 MERANGIN - Wirnadila, Nadya (MAT-EDUKASIA, 2017)
This study aims to describe the learning outcomes of mathematics using the Talking Stick learning model better than conventional learning. This study uses a quantitative approach to the experimental method with a population of class VII students of Merangin 10 Middle School. The sampling technique uses Simple Random Sampling. The selected sample is class VII F as the experimental class and VII G as the control class. The technique of collecting data through tests of mathematics learning outcomes in the form of essay questions with the number of six items in the quadrilateral material. The data analysis technique used to test the hypothesis was the t-test assisted by the IBM SPSS Statistics 21 program. From the analysis of the final test data in the experimental class it was obtained an average of 60.43, while the control class averaged 50.79. The hypothesis test results are known to be sig <  or 0.008 <0.05 , Ho is rejected and H1 is accepted. The conclusion of this study is that the learning outcomes of mathematics using the Talking Stick learning model are better than the conventional learning of class VII students of SMP N 10 Merangin.